Changes in the perceived quality of primary care in Shanghai and Shenzhen, China: a difference-in-difference analysis - Xiaolin Wei; Haitao Li; Nan Yang; Samuel YS Wong; Marc CS Chong; Leiyu Shi; Martin CS Wong; Jianguang Xu; Dan Zhang; Jinling Tang; Donald KT Li; Qingyue Meng; et al.
AbstractObjective To assess changes in the quality of primary care in two megacities following the introduction of health system reforms in China.Methods We conducted multistage stratified random face-to-face surveys of patients visiting community health centres in Shanghai in 2011 and 2013, and Shenzhen in 2012 and 2013. Quality of primary care was measured using an assessment tool. Difference-in-difference analyses based on multiple linear regressions were used to compare the changes over time, after controlling for potential confounders.Findings Most (2721) of the 3214 participants used a community health centre as their regular source of care and were included in our analyses. The mean total scores for quality of primary care were similar for Shanghai and Shenzhen at baseline. In Shenzhen, the mean total scores for all participants and those on low incomes had worsened by 0.922 (95% CI: 0.629 to 1.215) and 1.203 (95% CI: 0.397 to 2.009), respectively. In Shanghai, however, there were improvements in the mean total scores which included increases in the scores for first-contact utilization, continuity, coordination of information and comprehensiveness.Conclusion The quality of primary care improved in Shanghai but not in Shenzhen. This may be because, in Shanghai, beneficial long-term relationships between patients and general practitioners were supported by capitation payments and the provision of services tailored to the local health priorities.